Unexpected entanglement dynamics in semidilute blends of supercoiled and ring DNA. Issue 1 (27th November 2019) - Peddireddy, Karthik R.; Lee, Megan; Zhou, Yuecheng; Adalbert, Serenity; Anderson, Sylas; Schroeder, Charles M.; Robertson-Anderson, Rae M.
Abstract : Semidilute blends of supercoiled and ring DNA exhibit surprising entanglement dynamics both in linear and nonlinear regimes. Abstract : Blends of polymers of different topologies, such as ring and supercoiled, naturally occur in biology and often exhibit emergent viscoelastic properties coveted in industry. However, due to their complexity, along with the difficulty of producing polymers of different topologies, the dynamics of topological polymer blends remains poorly understood. We address this void by using both passive and active microrheology to characterize the linear and nonlinear rheological properties of blends of relaxed circular and supercoiled DNA. We characterize the dynamics as we vary the concentration from below the overlap concentration c* to above (0.5 c* to 2 c* ). Surprisingly, despite working at the dilute–semidilute crossover, entanglement dynamics, such as elastic plateaus and multiple relaxation modes, emerge. Finally, blends exhibit an unexpected sustained elastic response to nonlinear strains not previously observed even in well-entangled linear polymer solutions.